Correlation between microscopic and endoscopic approach to tympanoplasty: a comparative study - Rathod, Jitendra; Vare, Reena; Thomas, Annju (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: The objective of the study was to evaluate the role of endoscopes in the management of dry central perforations of the tympanic membrane, compare the visualization of middle ear anatomy, time taken for the procedure and each step of the surgery and preoperative and postoperative hearing results/improvement. Methods: Fifty patients of chronic suppurative otitis media without cholesteatoma who came to ENT OPD at MGM medical college and hospital Aurangabad were included. They were divided into 2 groups with 25 patients each. Group A underwent microscopic approach to tympanoplasty and group b underwent endoscopic approach to tympanoplasty. Patients were assessed pre and postoperatively after 7 days, 14 days, 1 month, 3 months and 6 months with postoperative audiometry in the third month. Results: There was an improvement in the post-operative audiometry air bone gap (ABG) in both the groups. The operative time for group A was comparatively lesser than group B. Residual perforation were detected in one patient in group A at postoperative months 3 and 6, and for group B at postoperative month 3 and in two patients at postoperative month 6. Conclusions: A shorter operative duration is an advantage of microscopic tympanoplasty technique. One handed technique is one of the disadvantages of endoscope. The endoscopic approach gave better results in terms of easy visualization of the entire tympanic membrane and ossicular system. Tympanoplasty using endoscope was found to be an effective method for management of dry central perforations of the tympanic membrane.